PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII SMPN 1 PARIGI TENGAH PADA MATERI PERBANDINGAN - Saputri, Rifka; Paloloang, Baharuddin; Hasbi, Muh. (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
The purpose of this study was to obtain a description of the application of the think talk write type of cooperative learning model to improve the learning outcomes of class VII students of SMPN 1 Parigi Tengah on Comparative Materials. This research is Classroom Action Research (CAR) which refers to the research design of Kemmis and Mc.Taggart (Arikunto, 2007:16) namely (1) planning, (2) action, (3) observation, and (4) reflection. Data collected in this study through observation sheets, interviews, field notes, and data on student learning outcomes. The subjects selected in this study were class VII students of SMPN 1 Parigi Tengah, totaling 24 students and 3 students were selected as informants. The results showed that there was an increase in student learning outcomes in comparative material in class VII SMPN 1 Parigi Tengah by following the stages of cooperative learning of the Think Talk Write type, namely: (1) Think, at this stage students read and observe the problem on the LKPD given by the teacher so that it helps students to be able to think about possible answers then write them down in a small note. (2) Talk, at this stage students discuss with their group friends about the results of the small notes they have made. (3) Write, students write down the results of the discussion on the worksheet provided (LKPD).